2017
DOI: 10.1007/s12265-017-9747-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Porcine Mitral Valve Scaffold for Tissue Engineering

Abstract: Decellularized scaffolds represent a promising alternative for mitral valve (MV) replacement. This work developed and characterized a protocol for the decellularization of whole MVs. Porcine MVs were decellularized with 0.5% (w/v) SDS and 0.5% (w/v) SD and sterilized with 0.1% (v/v) PAA. Decellularized samples were seeded with human foreskin fibroblasts and human adipose-derived stem cells to investigate cellular repopulation and infiltration, and with human colony-forming endothelial cells to investigate coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…It can be noted that the use of cardiac fibroblasts would have provided a superior representation of in vivo cells; however, other cardiovascular studies have also used HFFs . As a preliminary study, human foreskin fibroblast cells were chosen based on a study in bovines that found that neointimal tissues consisted of a large proportion of fibroblast‐like cells .…”
Section: Discussionmentioning
confidence: 99%
“…It can be noted that the use of cardiac fibroblasts would have provided a superior representation of in vivo cells; however, other cardiovascular studies have also used HFFs . As a preliminary study, human foreskin fibroblast cells were chosen based on a study in bovines that found that neointimal tissues consisted of a large proportion of fibroblast‐like cells .…”
Section: Discussionmentioning
confidence: 99%
“…All four valves close rapidly and completely under minimal reverse pressure, stretching to maintain full competence during diastole. During these opening and closing movements, the valve leaflets withstand cyclic strains as high as 50%, whereas despite the pressure difference across the closed valves, which imposes large load on their leaflets, leaflet prolapse is prevented by large coaptation of the leaflets, reaching up to 40% of their surfaces [18,[64][65][66][67][68]. Even though each of the four heart valves has its own individual unique anatomical, structural and constitutional features that are adapted to their specific localization and function, they share common structural, constitutional and functional features.…”
Section: The Aortic and Pulmonary Valve Leaflets Open Against The Aormentioning
confidence: 99%
“…Collagen VI has been shown to form distinct structures within the fibrosa, surrounding the dense collagen I fibers of this layer [76]. The total collagen content in normal valve leaflets is approximately 50-63% (dry tissue weight ratio) [68,71,79,80], and the elastin content is approximately 10-11% (dry tissue weight ratio), depending on the valve type (Table 3) [78,[80][81][82][83]. Previous studies have reported the relative percentages of collagen I, III, and V in normal human MV leaflets to be approximately 74, 24 and 2% of the total collagen content, respectively, whereas collagen IV and VI were below the detection limit of the technique used in those studies [72,77].…”
Section: The Aortic and Pulmonary Valve Leaflets Open Against The Aormentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges in translating the data from pre-clinical and clinical pilot trials that will ultimately be faced by all tissue engineering projects are also reviewed [4]. The experimental studies in this issue address a variety of topics within the heart valve field including two papers on the development of decellularised valves [5,6], the chemical fixation of bovine pericardium and the assessment of a new transcatheter heart valve [7,8]. Within the vascular field, there are two papers, the first addresses the use of an in vivo approach that utilises the host reaction to an implanted biomaterial for the generation of completely autologous tissues, while the second examines the use of intravascular echo as a tool to evaluate the changes within tissue-engineered valves implanted into sheep [9,10].…”
mentioning
confidence: 99%